Profitability in the Banking Sector: A Case from the State-Owned Banks of Indonesia - Maya Sari, Dewi; Mislinawati; Wahyuni, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Finding empirical proof of how asset management, liquidity, and leverage affect the profitability of Indonesian state-owned banks listed on the stock exchange is the aim of this study. The information used comes from SOE annual financial statements from 2016 to 2018. Based on sample selection criteria, a total of 39 firms were identified in this study. Multiple linear regression was used to evaluate the data. Based on the research results, profitability is positively impacted by asset management and liquidity, however leverage has a negative effect.